Healthcare governance in prisons in England: prisoners’ experiences of changes over time - Bowstead, Janet Christine (Critical public health, 2024)
According to international law, prisoners should have access to healthcare on an equivalent basis to the rest of the population, and the UK Government has stated its commitment to such equivalence. Healthcare provision in English prisons has seen several reorganisations, notably in 2006 and 2013, with the stated intentions of improving healthcare provision in prisons. This article focuses on prisoners’ reported experiences over the periods of changes in healthcare governance, with the aim of identifying whether there are improvements from their perspectives. Survey data from a sample of prisoners has been collected by HM Inspectorate of Prisons for over 20 years, and these data have been used for secondary analysis of prisoners’ health needs and experiences of healthcare in English prisons. Despite the reorganisations of healthcare governance, the trends from 2003 to 2019 are of increasing health needs of prisoners and decreasing initial access, ongoing access, and quality of healthcare provision. There is little indication of any improvements experienced by prisoners from the 2006 or 2013 reorganisations. Prisoners are widely recognised as having distinct healthcare needs, but the data analysis reveals demographic differences in health needs and health access within the prison population, and an overall decline in quality and accessibility of healthcare provision in English prisons.